Kapcsolat és különállás : a gazdasági gondolkodás mintázatai és megjelenésük Kautz műveiben - Barancsuk, János (Közép-Európai Közlemények, 2014)
The basic theory of the essay is that especially the Hungarian economic thinking has quite an offset parameter: the duality, which usually is the product of the effects coming from the main-stream angle, on the other hand the compulsive problem-solving methods created by the typical social economy’s happenings. This singularity originates form our systematic economic backward-ness and its impact on our ambitons to overtake but without any solid formula, according to the situation of the „non-royal way” go alongs. What factors do usually define the patterns of the views covered by the discipline? Wherein is it possible to originate the singularities from specific eras, peculiar conceptions and scientific evolutinos? How did the economic sciences and viewpoints become framed in our country during the period of Dualism? Were the representatives of some of our disciplines just followers, adaptors or in some cases, at specific areas even front-line fighters of the advancement of academic sciences? We try to give answers for these questions by analyzing the famous economist, Gyula Kautz’s work, who lived in the times of the Austro-Hungarian Compromise.